2022
DOI: 10.3389/fped.2022.922464
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Pathogenesis in Pediatric Multifocal Atrial Tachycardia

Abstract: Multifocal atrial tachycardia (MAT) is defined as irregular P-P, R-R, and P-R intervals, isoelectric baseline between P waves, and ventricular rate over 100 beats/min. Although the prognosis of pediatric MAT in most patients is favorable, adverse outcomes of MAT have been reported, such as cardiogenic death (3%), respiratory failure (6%), or persistent arrhythmia (7%), due to delayed diagnosis and poorly controlled MAT. Previous studies demonstrated that pediatric MAT is associated with multiple enhanced autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
1
0
0
Order By: Relevance
“…In addition, more serious fundamental conditions such as pulmonary illnesses and electrolyte problems were detected. The results for newborns with MAT are generally good, with the documented exception of cases with structural heart abnormalities or persistent rapid ventricular rate [17]. Our results also revealed that the MAT group had a greater risk of heart failure and stayed in the hospital longer than the other two groups.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, more serious fundamental conditions such as pulmonary illnesses and electrolyte problems were detected. The results for newborns with MAT are generally good, with the documented exception of cases with structural heart abnormalities or persistent rapid ventricular rate [17]. Our results also revealed that the MAT group had a greater risk of heart failure and stayed in the hospital longer than the other two groups.…”
Section: Discussionsupporting
confidence: 52%
“…In a systemic inflammatory state, the levels of inflammatory factors, such as TNF-α, interleukin-6 (IL-6), and interleukin-8 (IL-8), that reflect acute infection are significantly increased. Some scholars considered that the level of inflammatory factors reflecting acute infection may also have predictive value for AT [19].…”
Section: Discussionmentioning
confidence: 99%
“…Следует отметить, что в детском возрасте нозологические формы аритмий разнообразны. Особенности активности ВНС при формировании ряда НРС у взрослых, которые представлены выше, были обнаружены и в детском организме [56]. Тем не менее, хотелось бы сделать акцент на некоторых особенностях вегетативной дисфункции среди детей и подростков с аритмиями.…”
Section: вегетативная нервная система и нарушения ритма сердцаunclassified